A Photoredox Nozaki‐Hiyama Reaction Catalytic in Chromium. Issue 29 (12th May 2022) - Calogero, Francesco; Potenti, Simone; Magagnano, Giandomenico; Mosca, Giampaolo; Gualandi, Andrea; Marchini, Marianna; Ceroni, Paola; Cozzi, Pier Giorgio
Abstract: Organochromium(III) species are multipurpose nucleophiles used in the synthesis of complex organic molecules due to their high functional group tolerance and extraordinary chemoselectivity for aldehydes. The preparation of organochromium(III) species starting from organic halides requires the use of a stoichiometric amount of chromium(II) salts or a catalytic amount of chromium(III) salts in the presence of stoichiometric reductants (such as Mn(0)). Recently, radicals formation from readily available alkenes, followed by their trapping with stoichiometric or catalytic amount of chromium(II) salts were reported in photoredox conditions for the generation of Cr(III) organometallic species. In this paper we disclose a real Nozaki‐Hiyama reaction (NH) in which photoredox conditions enable the preparation of Cr(III) allyl reagents starting from available allyl halides and stable Cr(III) salts. Abstract : Allylation of aldehydes is possible by a real photoredox Nozaki‐Hiyama reaction starting from available allyl halides and stable Cr(III) salts.